Dysphagia and gastresophageal reflux in institutionalized elderly (Research, Society and Development, 2021)
Objective: The aim of this study was to identify the prevalence of gastroesophageal reflux and dysphagia in institutionalized elderly people. Method: This is a retrospective, analytical, quantitative documentary study, in which medical records of 191 institutionalized elderly people living in five long- stay institutions located in the city of João Pessoa-PB were consulted. The instrument used for data collection from medical records was a form elaborated for this purpose, adapted from the triage protocols RADI (Screening of Elder Oropharyngeal Dysphagia) and SSI (Index of Reflux Symptoms). The statistical analysis was performed to obtain measures of central and inferential tendency through the correlation tests and the Kolmogorov-Smirnov test was applied to test the normality of the sample distribution. To analyze the association  between the two dependent variables, having or not dysphagia and having or not reflux, Pearson’s chi-square tests or Fisher's exact text were applied. Results: Most of the study sample was composed of women (n=144 / 75.4%); among the elderly in the study group, the majority presented with some food refusal, delay to eat and difficulty to eat some food, and, the higher the age, the greater the presence of food refusal and weight loss in this age group. Conclusion: The elderly in the study showed a low presence of gastroesophageal reflux symptoms, with some associated signs and symptoms of dysphagia.